Identification of Species and Sources of Cryptosporidium Oocysts in Storm Waters with a Small-Subunit rRNA-Based Diagnostic and Genotyping Tool - Xiao, Lihua (American Society for Microbiology, 2000)
The identification of Cryptosporidium oocysts in environmental samples is largely made by the use of an immunofluorescent assay. In this study, we have used a small-subunit rRNA-based PCR-restriction fragment length polymorphism technique to identify species and sources of Cryptosporidium oocysts present in 29 storm water samples collected from a stream in New York. A total of 12 genotypes were found in 27 positive samples; for 4 the species and probable origins were identified by sequence analysis, whereas the rest represent new genotypes from wildlife. Thus, this technique provides an alternative method for the detection and differentiation of Cryptosporidium parasites in environmental samples.